Metabolomics study on the therapeutic effect of traditional Chinese medicine Xue-Fu-Zhu-Yu decoction in coronary heart disease based on LC-Q-TOF/MS and GC-MS analysis - Yi, Min; Li, Qiuxia; Zhao, Yuhang; Nie, Shanshan; Wu, Ning; Wang, Dongsheng (Drug metabolism and pharmacokinetics, 2019)
The present study aims is to investigate the metabolic mechanism of Xue-Fu-Zhu-Yu decoction (XFZYD) in the treatment of blood-stasis syndrome in Coronary Heart Disease (CHD). To that end, 30 CHD patients with Blood-Stasis Syndrome (BSS) and 20 healthy subjects were enrolled. LC-Q-TOF/MS analysis determined that in comparison between CHD with BSS patients (Group A) and healthy subjects (Group C), 59 significantly differential metabolites in the positive mode and 18 significantly differential metabolites in the negative mode. The metabolite constituents in the plasma of 30 CHD with BSS patients before (group A) and after 30 days of treatment (Group B), and 20 healthy subjects (Group C) were analyzed using LC-Q-TOF/MS and GC-MS. Based on multivariate statistical analysis (PCA, PLS-DA and OPLS-DA), we determined 69 differential metabolites. The levels of hemorheology indexes were significantly down-regulated after treatment. Metabolic pathway attribution analysis showed that lipid metabolism, amino acid metabolism and bile acid metabolism pathways are involved. Our study identifies the metabolic networks of CHD and demonstrates the efficacy of this metabolomics approach to systematically study the therapeutic effect of XFZYC on CHD. Xue-Fu-Zhu-Yu decoction (XFZYD) is a well-known formula of traditional Chinese medicine (TCM) for the treatment of cardiovascular-associated diseases in China and other East Asian countries. In the present study, a convenient, rapid and efficient method known as LC-Q-TOF-MS/MS was established to qualitatively and quantitatively investigate the metabolites constituents in the plasma of coronary heart disease patients. To that end, 30 CHD patients with Blood stasis syndrome were enrolled in this research. The blood samples of these CHD patients were collected before and after the 30-day treatment course of XFZYD. Samples were prepared before metabolomics analysis, and the different multi-constituents of metabolites were quantified by LC-Q-TOF-MS/MS. Retention time and MS spectra from blood plasma revealed compounds with significant different level (VIP>1.5; <0.05). The positive ion trace exhibited 38 differential metabolites, among which the concentrations of 24 compounds were significantly increased and the concentrations of 14 compound were significantly reduced after XFZYD oral treatment. The negative ion trace exhibited 12 differential metabolites, among which the levels of 9 compound were increased and the levels of 3 compounds were significantly reduced after treatment. Metabolic pathway attribution analysis showed that these differentially expressed compounds were located in amino acid metabolism and bile acid metabolism pathways. Taken together, the present study demonstrates the cardio-protective effects of XFZY and that the oral treatment with XFZYD is effective to improve the plasma chemical profile of CHD patients, thereby reversing the abnormal metabolic state to a near normal level. [Display omitted]